2019
DOI: 10.29252/archhygsci.8.3.178
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey of Cutaneous Leishmaniasis in Mazandaran Province, Northern Iran

Abstract: Background & Aims of the Study: Cutaneous leishmaniasis (CL) is considered one of the most important human vector-borne diseases in Iran. The current study aimed to determine some epidemiological aspects of cutaneous leishmaniasis in Mazandaran, Northern Iran. Materials and Methods: This descriptive study was conducted using the epidemiological data, including demographic and clinical features collected from 379 patients diagnosed with leishmaniasis in health centers affiliated to the Deputy for Health Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
5
1
Order By: Relevance
“…In the present study, most of the patients were male, which is in accord with the results of other studies in Golestan ( Jorjani et al, 2019 ), Mazandaran ( Ghavibazou et al, 2019 ), Northkhorasan ( Alavinia et al, 2009 ) and Qom ( Rostami et al, 2013 ) provinces, and also the study carried out over four decades in Iran ( Piroozi et al, 2019 ). The higher leishmaniasis cases in men seems to be due to more outdoor activity and less coverage compared with women wearing Hijab in Muslim countries, leading to being bitten more by sand flies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, most of the patients were male, which is in accord with the results of other studies in Golestan ( Jorjani et al, 2019 ), Mazandaran ( Ghavibazou et al, 2019 ), Northkhorasan ( Alavinia et al, 2009 ) and Qom ( Rostami et al, 2013 ) provinces, and also the study carried out over four decades in Iran ( Piroozi et al, 2019 ). The higher leishmaniasis cases in men seems to be due to more outdoor activity and less coverage compared with women wearing Hijab in Muslim countries, leading to being bitten more by sand flies.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in accordance with studies conducted in Golestan ( Jorjani et al, 2019 ) and Kerman ( Khosravi et al, 2017 ) provinces, in northern and southeastern Iran, respectively. However, contradict with studies conducted in the areas with low endemicity of CL such as Mazandaran ( Ghavibazou et al, 2019 ), in northern and Kashan ( Moein et al, 2018 ), in central Iran, which reported the highest incidence in the age group of 20–29 years. It is worth noting that when the endemicity of a certain disease is high (as in the current study), the disease is more common in younger age groups.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Mazandaran Province is considered as one of the sporadic foci of leishmaniasis. In previous studies, sporadic cases of cutaneous and visceral leishmaniasis have been documented in some parts of the Province ( 18 – 20 ), some of which have a history of travel to endemic areas of leishmaniasis. Since Mazandaran Province borders with the provinces that are endemic foci of the disease, disregarding the characteristics of the vectors can lead to an increase in the incidence of this disease.…”
Section: Introductionmentioning
confidence: 99%